Not for free : - Berman, Saul Jay (Harvard Business Review Press, 2011)
It used to be only dotcom start-ups lacked workable business models. But now the ubiquity of cheap communications and computing is deeply wounding business models across the board. Combined with rapidly changing customer expectations, the rules for how value is delivered, and what, when, and how much customers will pay are in flux.